STUDI VARIASI KOMPOSISI BAHAN DASAR BRIKET DARI SAMPAH ORGANIK PASAR - Rusdiana Setyaningtyas; Anis Artiyani (HEXAGON, 2018)
The composition of waste that dominates the most urban areas is organic waste with a composition of ± around 70%. This organic waste can be used in an effort to reduce the amount of waste, especially waste originating from fruits and vegetables. One alternative for the utilization of fruit and vegetable waste is used as a briquette base.This study aims to obtain the best composition in the manufacture of briquettes from market organic waste consisting of a mixture of fruit and vegetable waste. Briquette testing is carried out with various variations in the composition of the use of fruit and vegetable waste with treatment using a ratio of 0%: 100% (B0S4), 75%: 25% (B3S1), 50%: 50% (B2S2), 25%: 75% (B1S3) and 100%: 0% (B4S0). Briquette quality parameters used are water content, ash content and heating value. The results showed that the best briquettes were found in composition variation (B0S4), namely 0% fruit waste: 100% vegetables with a moisture content value of 5.67%, ash content value of 10.33% and a heating value of 5645.52 cal/gram .